2012
DOI: 10.1097/sla.0b013e318265ea13
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy Timing

Abstract: In this series, appendectomy delay did not increase the risk of perforation but was associated with a significantly increased risk of SSI in patients with nonperforated appendicitis. Prompt surgical intervention is warranted to avoid additional morbidity in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
2
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(63 citation statements)
references
References 5 publications
1
54
2
6
Order By: Relevance
“…Time from admission to operation of more than 6 h was not associated with the development of SSI in contrast to a large study by Teixeira et al [11]. In that study, however, no information regarding the duration of symptoms is reported.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Time from admission to operation of more than 6 h was not associated with the development of SSI in contrast to a large study by Teixeira et al [11]. In that study, however, no information regarding the duration of symptoms is reported.…”
Section: Discussioncontrasting
confidence: 53%
“…Continuous data were dichotomized using clinically relevant cut-off points or based on previous publications [11,12,14]. After univariable analysis, factors with a p value of <0.30 were selected for multivariable analysis and entered in a logistic regression model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][49][50][51][52][53] The results of our study demonstrate that appendectomy is infrequently performed after hours in Canadian tertiary hospitals, although variation across sites does exist. This practice variation could be explained by site-specific surgical policies or established management pathways, resource availability, or the use of ED observation units.…”
Section: Discussionmentioning
confidence: 77%
“…Development of the postoperative intra-abdominal abscess after appendectomy, is a rare, but it's a serious complication and is associated with significant morbidity (24). Some reports (25)(26)(27) A, The appendix was put inside the reusable retrieval bag, before closure its mouth and extraction from the abdominal cavity. B, The reusable retrieval bag with the appendix inside was extracted through port without contact with wound or contamination of abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%